2019
DOI: 10.17275/per.19.9.6.2
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of online privacy concerns of teacher candidates

Abstract: Examining the online privacy concerns of our prospective teachers who will raise our future generations is important in terms of determining and increasing the awareness levels of prospective teachers of the digital world and for the development of a conscious generation having this awareness while raising students. The definition of cyber space or virtual environments has further expanded; digital business applications, online services, online training systems, e-commerce sites, social media sites, and surely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This result differs from the results of other studies in the literature. Some studies found that privacy concerns decrease as the grade level increases (Ağırtaş & Güler, 2020;Korucu & Gürkez, 2019) or that there is no relationship between the grade variable and privacy concerns (Okumuş & Atılgan, 2021). The results obtained from this research show that first-year students have lower online privacy concerns.…”
Section: Medi̇admentioning
confidence: 52%
“…This result differs from the results of other studies in the literature. Some studies found that privacy concerns decrease as the grade level increases (Ağırtaş & Güler, 2020;Korucu & Gürkez, 2019) or that there is no relationship between the grade variable and privacy concerns (Okumuş & Atılgan, 2021). The results obtained from this research show that first-year students have lower online privacy concerns.…”
Section: Medi̇admentioning
confidence: 52%
“…Another finding that may be related to social phobia in online learning environments is that digital skills reduce autonomy anxiety in online environments. (Korucu & Gürkez, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding that may be related to social anxiety in online learning environments is that digital skills reduce autonomy anxiety in online environments. (Korucu & Gürkez, 2019). Gender is also an important variable in e-learning environments, and students' anxiety may vary according to gender.…”
Section: Introductionmentioning
confidence: 99%